Educación sexual integral en el desarrollo de la autoestima de los estudiantes de séptimo grado EGB, paralelo “A” de la Unidad Educativa Fiscomisional “Doctor Gabriel García Moreno” periodo académico 2021 – 2022 - Mañay Sampedro, Daniela Alexandra (2022)
Mañay Sampedro D (2022). Comprehensive sexual education in the development of self- esteem of seventh grade EGB students, parallel "A" at UNIDAD EDUCATIVA FISCOMISIONAL "Doctor Gabriel García Moreno" academic period 2021 - 2022. (Grade thesis). National University of Chimborazo, Riobamba, Ecuador. Sexuality is a right and an educational content that contributes to the progress of free, healthy and responsible students, it also helps to build relationships free of discrimination and violence. At “Doctor Gabriel García Moreno" located in Guano city; this is one of the most controversial aspects that affects the integral sexual development., According to the analysis of the data obtained, there is no progress of the self-esteem in the students since teachers do not have a good initiative to continue with the class, and prepare to put into practice methodologies that solve the problem that many children do not have sufficient knowledge about comprehensive sexual education in the educational field, the design of the research is qualitative of a non-experimental nature, its level is descriptive, bibliographic and field, with a population of 27 students and 4 teachers, the technique used is a survey and the instrument is a structured questionnaire, and the low self-esteem of the students is determined. children in the educational unit, with this a proposal of a socialization is proposed with the application of a video QUIZ, with issues of sexuality and values, concluding that the research is a significant contribution to the interface of students and teachers in sexual education issues, and it is recommended to promote the application of similar terminologies in the educational unit, leaving this as a precedent for future research.